celebrity endorsement sebagai strategi digital marketing pada aqiqah nurul hayat surabaya ditinjau dari perspektif etika bisnis islam - Pur Wulan Septy, Hilda Tri; Canggih, Clarashinta (Jurnal Ekonomika dan Bisnis Islam, 2022)
This research aimed to find out the digital marketing strategy in Aqiqah Nurul Hayat through endorsements. In addition, this study also aimed to determine the conformity of endorsement activities with the concept of Islamic business ethics. This study used qualitative research methods i.e. field research and library research. The data was collected through interview, observation, and documentation. The results indicate that Aqiqah Nurul Hayat's digital marketing strategy is through endorsements on social media (instagram and tiktok). This strategy is able to expand market reach as proved by increased Instagram engagement through the number of likes, comments, shares, views, and reposts. However, the agreement between the celebrity and Aqiqah Nurul Hayat who uses the barter system is still considered weak. The results show that, the implementation of celebrity endorsement at Aqiqah Nurul Hayat is not following the principles of responsibility and truth under the concept of Islamic business ethics, whereby sometimes some celebrities do not carry out their obligations in accordance with the terms and conditions of the endorsement. However, the principles of unity, balance, and free will are in accordance with the principles of Islamic business ethics whereby the endorsement procedure benefitted both parties through negotiations and freedom of opinion while conducting business.